Analysis of prognostic factors for melanoma patients - Lideikaitė, Andrė; Mozūraitienė, Julija; Letautienė, Simona (Acta medica Lituanica, 2017)
Introduction. Melanoma is the most dangerous form of skin cancer. Morbidity from melanoma is increasing every year. Previous studies have revealed that there are some demographic and clinical factors having effect on melanoma survival prognosis. Aim of the study. Purpose of our study was to assess melanoma survival depending on prognostic factors, such as age, sex, stage, depth, histology and anatomical site. Materials and methods. We investigated melanoma-specific survival up to 10 years in 85 primary cases of melanoma from diagnosis at the National Cancer Institute in 2006. Analysis was performed for one-, five-, and ten-year survival. The data were processed with Microsoft Excel, data analysis was conducted using SPSS® software. Results. Melanomas diagnosed at stage IV or thicker than 4.00 mm had lower survival (five-year survival: 12.5% and 26.66%, respectively). A significant survival difference was observed among the different stages (p = 0.003) and different depths (p = 0.049) of melanoma. Ten-year survival was 32% for men and 61% for women, but melanoma-specific survival dependent on sex did not have a statistically significant difference (p = 0.121). In persons diagnosed at the age of 65 or older, ten-year survival was lower than in those of 40–64 years of age and in the  age group of 15–39 years (44.44% and 26.66%, respectively), but melanoma-specific survival in different age groups did not have a statistically significant difference (p = 0.455). Back/breast skin melanoma had lower ten-year survival (37.03%) than other anatomic sites. Nodular melanoma had the poorest five-year and ten-year melanoma-specific survival among histological subtypes (51.67% and 38.75%). The differences between melanoma localizations (p = 0.457) and histological types (p = 0.364) were not statistically significant. Conclusions. Lower melanoma-specific survival rates were observed among patients diagnosed at a late stage, older age, and when melanomas were thicker than 4.00 mm. Female and younger patients had better melanoma-specific survival than men and older people, and these differences were statistically significant. Melanoma diagnosed at an early stage and of a  small depth had higher survival rates. Back/breast skin melanoma had poorer prognosis than other anatomic sites. Nodular melanoma had the  lowest melanoma-specific survival, while superficial spreading or lentigo maligna had the best prognosis among histological subtypes. However, differences in melanoma survival in different sex and age groups, localizations and histological types were not statistically significant.
Keywords: melanoma; survival; histology; anatomic sites